2018
DOI: 10.3390/brainsci8060107
|View full text |Cite
|
Sign up to set email alerts
|

Brain Connectivity Networks and the Aesthetic Experience of Music

Abstract: Listening to music is above all a human experience, which becomes an aesthetic experience when an individual immerses himself/herself in the music, dedicating attention to perceptual-cognitive-affective interpretation and evaluation. The study of these processes where the individual perceives, understands, enjoys and evaluates a set of auditory stimuli has mainly been focused on the effect of music on specific brain structures, as measured with neurophysiology and neuroimaging techniques. The very recent appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 85 publications
1
50
0
3
Order By: Relevance
“…Other authors proposed that the same circuits might underlie the human ability to appreciate the intrinsic value of beautiful objects (Ishizu & Zeki, 2013;Kawabata & Zeki, 2004). Through a DTI and probabilistic tractography study (Sachs et al, 2016), it has been shown that aesthetic emotions triggered by music are related to the structural connectivity between associative auditory cortices and the frontal reward-related areas (such as the anterior insula and the medial prefrontal cortex; for a review of functional connectivity studies supporting this evidence refer to Reybrouck et al, 2018). Mnecke and colleagues, in a very elegant study exploring the aesthetic appreciation of atonal music and its relation with learning mechanisms, suggested that the dopaminergic activity may mediate the reward generated in response to representational models' refinement (Mencke et al, 2019).…”
Section: How Beauty Makes Us Curious: Aesthetic Value and The "Knowlementioning
confidence: 99%
“…Other authors proposed that the same circuits might underlie the human ability to appreciate the intrinsic value of beautiful objects (Ishizu & Zeki, 2013;Kawabata & Zeki, 2004). Through a DTI and probabilistic tractography study (Sachs et al, 2016), it has been shown that aesthetic emotions triggered by music are related to the structural connectivity between associative auditory cortices and the frontal reward-related areas (such as the anterior insula and the medial prefrontal cortex; for a review of functional connectivity studies supporting this evidence refer to Reybrouck et al, 2018). Mnecke and colleagues, in a very elegant study exploring the aesthetic appreciation of atonal music and its relation with learning mechanisms, suggested that the dopaminergic activity may mediate the reward generated in response to representational models' refinement (Mencke et al, 2019).…”
Section: How Beauty Makes Us Curious: Aesthetic Value and The "Knowlementioning
confidence: 99%
“…By comparing the AD anatomic pathogenesis (for review see Veitch et al [52]) with the functional activations of various longterm musical memories, we should be able to explain the peculiar pathological progression of long-term musical memories in AD patients across all stages. An important literature exists concerning the exploration of musical cognition [18,[70][71][72][73][74] with neuroimaging methods. However, experimental works specifically focusing on musical memory are much scarcer [75][76][77] and mainly done in healthy subjects.…”
Section: Contribution Of Neuroimaging Resultsmentioning
confidence: 99%
“…Similarly to other pleasant activities, music listening has been associated with a cyclical time course of pleasure including: a phase of expectation or wanting for a specific rewarding musical structure; a phase of consummation or liking of the music reward, which can have a peak level of pleasure (e.g., musical chills); a satiety or learning phase, where one learns and updates musical predictions changing both the wanting phase and the liking phase for future listening experiences (Gebauer et al 2012;Georgiadis and Kringelbach 2012;Kringelbach et al 2012;Brattico et al 2013;Brattico 2015Brattico , 2019a. These musical pleasure cycles, driven by different mechanisms including musical expectancy, memory associations, evaluative conditions (for a review, see Gebauer et al 2012;Brattico 2019b), involve the reward brain system, in particular the OFC, the ventral tegmental area, and the nucleus accumbens (Blood and Zatorre 2001;Brown et al 2004;Menon and Levitin 2005;Koelsch et al 2006;Suzuki et al 2008;Osuch et al 2009;Brattico et al 2015;Liu et al 2016Liu et al , 2017Reybrouck et al, 2018). All these areas are similarly engaged in other pleasurable experiences involving food or sex (Georgiadis & Kringelbach, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…showing that real-world music listening is associated with neural connectivity patterns rather than activity in isolated regions (Pfeifer and Allen 2012;Reybrouck et al 2018). However, despite the important role that music listening plays in the lives of children and adolescents, none of the previous neuroimaging studies has so far investigated the neural underpinning of naturalistic music listening (not interrupted by behavioral tasks) in this young population.…”
Section: Introductionmentioning
confidence: 99%